2011
DOI: 10.1063/1.3572236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface preparation and interfacial layer on the quality of SiO2/GaN interfaces

Abstract: In this work, SiO2/GaN MOS structures have been fabricated using Electron Cyclotron Resonance Plasma Enhanced Chemical Vapor Deposition (ECR-PECVD) for deposition of silicon dioxide (SiO2) at low temperature (300 °C) on N-type, NID and P-type GaN epitaxial layers. Surface preparation involving chemical, UV-Ozone oxidation and oxygen plasma oxidation have been investigated by XPS analysis of the GaN surfaces prior to SiO2 deposition. The association of UV ozone and plasma oxidation allows a complete removal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“… Silylation is used in many instances to render silica surfaces hydrophobic, which it does by capping the silanol groups (Si–OH) present on the surface. , Because those moieties act as nucleation sites during the chemical deposition of solid films, silylation can also be used to inhibit ALD processes . Regarding radiation with ultraviolet (UV) light while in the presence of ozone, this is known to oxidize organic matter, and is therefore commonly used to clean solid surfaces. In our study, we were able to demonstrate that mild UV/O 3 treatments are capable of removing the silylation agents from SiO 2 films and to reinstate their reactivity toward ALD . A combination of both steps can therefore afford the selective activation and deactivation of ALD processes on silicon oxide surfaces .…”
Section: Introductionmentioning
confidence: 71%
“… Silylation is used in many instances to render silica surfaces hydrophobic, which it does by capping the silanol groups (Si–OH) present on the surface. , Because those moieties act as nucleation sites during the chemical deposition of solid films, silylation can also be used to inhibit ALD processes . Regarding radiation with ultraviolet (UV) light while in the presence of ozone, this is known to oxidize organic matter, and is therefore commonly used to clean solid surfaces. In our study, we were able to demonstrate that mild UV/O 3 treatments are capable of removing the silylation agents from SiO 2 films and to reinstate their reactivity toward ALD . A combination of both steps can therefore afford the selective activation and deactivation of ALD processes on silicon oxide surfaces .…”
Section: Introductionmentioning
confidence: 71%
“…An optimized process for reduced interface state density at the oxide/n-type semiconductor interface is unlikely to be directly transferrable to a p-type GaN device. In fact, reference [ 129 ] demonstrates that for similar interface preparation steps for each GaN doping type (n-type, p-type and unintentionally doped), the optimization of the surface preparation is strongly dependent on the GaN doping type.…”
Section: Discussionmentioning
confidence: 99%
“…The high-low frequency method or conductance method, which do not require a theoretical profile to compare with the measured profile, can be considered to reduce the uncertainty associated with doping concentration in CV characterizations of the GaN MOS system. However, due to high series resistance and system noise, very few quasi-static or low (below 100 Hz) frequency CV profiles have been reported to date [ 94 ] and the conductance method can only measure interface states with short emission times [ 85 ]. The method developed for SiC—a photo-assisted CV measurement—was used by Wu et al on GaN [ 95 ] and measurements taken at varying temperatures were demonstrated in references [ 96 ] and [ 97 ].…”
Section: Gan Mosmentioning
confidence: 99%
“…There are many candidates for dielectric films of GaN MOSFETs, such as Ga 2 O 3 , SiO 2 , Al 2 O 3 , Gd 2 O 3 , HfO 2 , and AlN . In general, a material with large conduction‐band offset is suitable for the dielectric films since it suppresses the leakage current.…”
Section: Introductionmentioning
confidence: 99%